Are Salivary Gland Ultrasonography Scores Associated with Salivary Flow Rates and Oral Health-related Quality of Life in Sjogren Syndrome? - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2020)
Objective. Major salivary gland ultrasonography (SGUS) is a widely used imaging technique to evaluate salivary gland involvement in primary Sjogren syndrome (pSS). The aim of this study was to evaluate the relationship between SGUS, salivary flow rate (SFR) as an objective measure of the gland function, and oral health-related quality of life (OHRQOL) as a patient-reported outcome measure (PROM) in a pSS cohort. Methods. Sixty-six patients with pSS were examined by SGUS according to Hocevar and Milic scoring systems. Patients with inhomogeneity/hypoechoic areas with scores >= 2 in parotid and submandibular glands were classified separately as severe glandular involvement. Further, oral health, SFR, and Oral Health Impact Profile-14 (OHIP-14) for OHRQOL were assessed. Results. Both total Hocevar and Milic scores were higher in 21 pSS patients with low unstimulated whole salivary flow rate (U-WSFR) than 45 pSS patients without low U-WSFR (P = 0.001 and P < 0.0001, respectively). Increased scores of homogeneity, hypoechoic areas and glandular border visibility were observed in patients with low U-WSFR (P < 0.05). Among these variables, homogeneity score was found to be an independent risk factor for low U-WSFR in pSS according to logistic regression analysis (OR 1.586, P = 0.001). Moreover, a higher OHIP-14 score was observed in severe parotid involvement compared to nonsevere cases (23.26 +/- 21.19 vs 8.32 +/- 13.82, P = 0.004). Conclusion. High Milic and Hocevar SGUS scores are associated with reduced SFR and poor OHRQOL as a PROM. The inhomogeneity component of the SGUS score is associated with low U-WSFR and is an indicator of severely affected gland function.
Keywords: salivary glands; Sjogren syndrome; ultrasonography; CLASSIFICATION CRITERIA; DIAGNOSTIC-VALUE; SIALOGRAPHY; ULTRASOUND; CONSENSUS; TOOL